Interleukin-2 liposomes for primary immune deficiency using the aerosol route - Ten, R.M; Anderson, P.M; Zein, N.N; Temesgen, Z; Clawson, Mary Lou; Weiss, W (International immunopharmacology, 2002)
This is the first report of aerosol interleukin 2 (IL-2) liposome administration to individuals with immune deficiency. Parenteral IL-2 therapy has shown beneficial effects in some patients with cancer, common variable immunodeficiency (CVID), and human immunodeficiency virus (HIV) but is problematic because of side effects including fever and malaise as well as local swelling (delayed type hypersensitivity like reaction) after each subcutaneous IL-2 injection. Provision of an IL-2:human albumin liposome formulation via the aerosol route had few side effects in a recent clinical trial in cancer patients. Details of good manufacturing practice (GMP) synthesis and analysis of IL-2 liposomes ( N=6 lots) made without albumin carrier protein and placebo liposomes (three lots) are presented. After centrifugation, IL-2 was closely associated with the liposome pellet (99%). Mean diameter of liposomes was 1.1 μm. Patient acceptance, safety, toxicity, and immune effects of IL-2 liposomes were studied in individuals with primary immune deficiency ( N=15) and subsequently, a larger cohort of patients with hepatitis C. Experience in the immune deficient patients is the subject of this report. Placebo liposomes (12 weeks) and IL-2 liposomes (12 weeks) were provided using a nebulizer. Aerosol placebo liposomes and IL-2 liposomes were well tolerated. No changes in chest X-ray or pulmonary function were seen. Since biologic activity of aerosol IL-2 liposomes has been seen in viral disease (hepatitis C), additional studies of aerosol IL-2 liposomes in individuals with hepatitis C and HIV are planned.